SEBERAPA PENTING AUDIT REPORT LAG DI PEMERINTAH DAERAH PERLU DIUNGKAPKAN? - Khoirul Fuad; Amalia Septiana Dela Wiradinata (Dinamika Akuntansi Keuangan dan Perbankan, 2020)
The certainty of disclosing local government financial reports to the public in a timely manner is one of the main factors of a local government's success in financial management. This is because financial reports are used by the public to evaluate the management capabilities of existing resources. The public wants to ensure that these resources are managed effectively and efficiently. Additionally, the accuracy of local government financial reports disclosure is also used as a basis for future decision making. This study will examine several indicators related to the time of local government financial reports disclosure in Central Java during 2015 - 2017. This study used a measure of the effectiveness of internal audit, local government measurement from the perspective of audit opinion in each region. The data in this study were secondary data, namely the audit report of the financial audit agency (LHP BPK) from each local government. Furthermore, it also comprised the performance report of state development audit agency (LKjIP BPKP) in Central Java. The data obtained will be processed using Eviews 9 analysis tool. The results of this study indicate that the Internal Audit has no significant negative effect on the Audit Lag Report, the Size of the Local Government has no significant negative effect on the Audit Report Lag, and the Audit Opinion has no significant negative effect on the Audit Report Lag. Keywords: Audit Report Lag, Internal Audit, Local Government Measurement, Audit Opinion.